NMDA Receptors Regulate the Structural Plasticity of Spines and Axonal Boutons in Hippocampal Interneurons - Perez-Rando, Marta; Castillo-Gómez, Esther; Guirado, Ramon; Blasco-Ibañez, José Miguel; Crespo, Carlos; Varea, Emilio; Nacher, Juan (Frontiers in Cellular Neuroscience, 2017)
N-methyl-D-aspartate receptors (NMDARs) are present in both pyramidal neurons and interneurons of the hippocampus. These receptors play an important role in the adult structural plasticity of excitatory neurons, but their impact on the remodeling of interneurons is unknown. Among hippocampal interneurons, somatostatin-expressing cells located in the stratum oriens are of special interest because of their functional importance and structural characteristics: they display dendritic spines, which change density in response to different stimuli. In order to understand the role of NMDARs on the structural plasticity of these interneurons, we have injected acutely MK-801, an NMDAR antagonist, to adult mice which constitutively express EGFP in these cells. We have behaviorally tested the animals, confirming effects of the drug on locomotion and anxiety-related behaviors. NMDARs were expressed in the somata and dendritic spines of somatostatin-expressing interneurons. Twenty-four hours after the injection, the density of spines did not vary, but we found a significant increase in the density of their en passant boutons. We have also used entorhino-hippocampal organotypic cultures to study these interneurons in real-time. There was a rapid decrease in the apparition rate of spines after MK-801 administration, which persisted for 24 hours and returned to basal levels afterwards. A similar reversible decrease was detected in spine density. Our results show that both spines and axons of interneurons can undergo remodeling and highlight NMDARs as regulators of this plasticity. These results are specially relevant given the importance of all these players on hippocampal physiology and the etiopathology of certain psychiatric disorders.